Al-Daurul-iqtsishady lil-masharif al-islamiyah bainal-nadhariyah wal-tathbiq - ABUZAID, Muhammad Abdul Mun'im (Al-Ma'had Al-Alamy, Kairo, 1996)
Al-Daurul-iqtishady lil-masharif al-islamiyah bainal-nadhariyah wal-tathbiq